Maxillary distalization with miniscrews and leveling of the curve of Spee in dentoalveolar bimaxillary protrusion: a case report - Palacios Carpio , Keila (2026)
Dentoalveolar biprotrusion represents a therapeutic challenge when aiming to correct incisor protrusion while preserving facial esthetics. While conventional protocols often require extractions, the use of skeletal anchorage provides an effective alternative in selected cases. This case report describes the orthodontic management of an 18-year-old male patient with dentoalveolar biprotrusion, bilateral Class II interarch discrepancy, and an accentuated mandibular curve of Spee. Treatment was carried out using self-ligating fixed appliances, maxillary arch distalization assisted by infrazygomatic extra-alveolar miniscrews, and controlled leveling of the curve of Spee through intrusion mechanics with a utility arch. At the end of treatment, bilateral Class I molar and canine relationships were achieved, along with a reduction in dentolabial protrusion, adequate mandibular leveling, and maintenance of the vertical skeletal pattern, without clinically significant periodontal or radicular side effects. In conclusion, this biomechanical approach represents a predictable non-extraction option for the management of dentoalveolar biprotrusion when appropriate case selection and individualized planning are applied. The obtained outcomes are consistent with the available scientific evidence regarding the use of extra-alveolar miniscrews in such treatments.